FEATURES OF THE LOGISTICS OF CEMENT AS A GOOD - Самойленко, Антоніна; Крамаренко, Олексій (SWorldJournal, 2024)
In the article, the logistical ways of supplying cement by various types of available transport. The choice of vehicles and routes is crucial for cement logistics, as this material is heavy and bulky. The main types of transport for transporting cement ar